Effects of mean shear stress on the torsional fatigue strength of a spring steel with small scratches. (January 2020) - Nishimura, Y; Yanase, K; Tanaka, Y; Miyamoto, N; Miyakawa, S; Endo, M
The torsional fatigue behavior of a high-strength spring steel, SWOSC-V, was investigated. Of particular interest were the influences of small scratches and superimposed static shear stress in the very high cycle fatigue regime. To achieve the research objectives, an ultrasonic torsional fatigue testing machine was developed. S-N curves showed the fatigue limit for the tested material condition (i.e. with no residual stresses at specimen surface). This study revealed that a notable influence of the stress ratio, R, on the torsional fatigue behavior was not explicitly recognized. Concerning the influence of small scratches, it was found that thearea -parameter model can predict the lower bound of the torsional fatigue limit, irrespective of the value of R .